Highly efficient zirconium based carbonaceous solid acid catalyst for selective synthesis of 5-HMF from fructose and glucose in isopropanol as a solvent - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2022)
A new zirconium based carbonaceous solid acid catalyst Zr@CC-PA with both Lewis and Bronsted acidic sites was prepared by simultaneous carbonization and phosphonation of glucose followed by incorporation of zirconium metal on the surface of the catalyst. The catalyst was easy to prepare and the synthesized catalyst was well characterized using different techniques such as FT-IR, P-XRD, EDAX, SEM, TEM and XPS analysis. The catalytic activity was evaluated for synthesis of a very important platform chemical 5-HMF from fructose to glucose using isopropanol as a solvent. The catalyst was found to be highly efficient giving 86% yield of 5-HMF from fructose and 45% yield from glucose with high selectively. The catalyst can be reused at least four times without depreciation in its catalytic activity. The catalytic method developed is efficient, green and economical.
Keywords: 5-Hydroxymethylfurfural; fructose; glucose; Zirconium based